Sulfur Hosts against the Shuttle Effect. Issue 6 (11th April 2018) - Wang, Yazhou; Huang, Xiaoxiao; Zhang, Shanqing; Hou, Yanglong
Abstract: Lithium–sulfur (Li–S) batteries are considered as a substitute for conventional batteries as they are the most promising next‐generation energy‐storage system due to their high energy densities. However, their short cycling life, limited sulfur loading, severe polysulfide shuttling, and low sulfur utilization critically impede grid‐level‐storage energy techniques in Li–S batteries. The lithium shuttle effect results in rapid capacity fading and battery failure. The design and fabrication of sulfur hosts are key points to eliminate the aforementioned issues, especially the shuttle effect. In the past decade, spatial encapsulation and chemical interaction have improved the adsorption capacity of lithium polysulfides for the sulfur hosts and thus prolonged the lifetime of Li–S batteries. In an attempt to promote future research on the sulfur cathode and foster breakthroughs in Li–S batteries, recent achievements are highlighted, mechanical insights are discussed, and the remaining challenges and future research directions in the innovation of sulfur cathodes are identified. Abstract : The design and fabrication of sulfur hosts are critical to achieve practical applications of Li–S batteries. In an attempt to bridge the rational designs and the future research on sulfur cathodes, the recent progress is highlighted, mechanical insights are discussed, and the remaining challenges and future research directions are considered regarding the innovation of sulfur cathodes.